2019
DOI: 10.1021/acssuschemeng.9b03339
|View full text |Cite
|
Sign up to set email alerts
|

Reclaimed Rubber in Situ Grafted with Soybean Oil as a Novel Green Reactive Plasticizer in SBR/Silica Compounds

Abstract: Polymer recycling and biodegradable polymeric materials are two major routes toward the sustainable development of polymer materials which contribute to the management of waste. In this regard, an eco-friendly approach is presented wherein a high reclaiming degree of ground tire rubber (GTR) was achieved by low-temperature oxidation under the swollen action of soybean oil. In situ reclaimed GTR with soybean oil was cured into a reactive plasticizer (RP) through a free-radical chain reaction between activated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…On the other hand, some drawbacks are related to the processing of obtained products. This issue can be resolved by the application of plasticizers, such as bitumens [ 20 ] or petrochemical and renewable oils [ 21 , 22 , 23 ]. The application of thermoplastics is another possibility to enhance the processing of GTR and the performance of obtained materials [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some drawbacks are related to the processing of obtained products. This issue can be resolved by the application of plasticizers, such as bitumens [ 20 ] or petrochemical and renewable oils [ 21 , 22 , 23 ]. The application of thermoplastics is another possibility to enhance the processing of GTR and the performance of obtained materials [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This also demonstrates that the amount of active –OH bonds on the silica surface are effectively shielded by an appropriate amount of PEG. The variation of the peak shape at 2990, 2920 and 2860 cm −1 , which correspond to the asymmetrical stretching vibration and the symmetrical stretching vibration of methylene group [ 31 , 32 , 33 ], shows another confirmation of the appearance of different amounts of organic groups on the modified silica surface.…”
Section: Resultsmentioning
confidence: 98%
“…In fact, numerous reports have shown that modified vegetable oils can significantly improve the processability of silica-filled elastomer composites. [9][10][11][12]26,27 Given the increased use of (modified) vegetable oils in the rubber industry, there is an urgent need to understand how these oils interact with silica (as well as with other components in rubber compounds) and how chemical modification affects their performance. Although improved processability is generally attributed to the formation of hydrogen bonding (HB) between polar groups (e.g., epoxy) in modified vegetable oils and silanol groups present on the silica surface, direct evidence of such interactions is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…With climate change increasingly tangible, the sustainability of industrial production is emphasized more than ever. , For example, silica, a reinforcing filler frequently used in the manufacturing of tires, is now partially produced from rice husks. , Similarly, it has recently been shown that vegetable oils such as soybean oil (SBO) are promising alternatives to conventional rubber processing aids such as treated distillate aromatic extracts (TDAEs). Chemically modified SBOs can be synthesized through the controlled epoxidation of SBO. The use of vegetable oils provides many benefits. For example, vegetable oils are generally recognized for their attractive safety profile related to humans, animals, and the environment , and for reducing our dependence on petroleum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation